Development of a dynamic hitch lift controller using a hybrid control strategy in a heavy combination vehicle - Abdul Manaf, Muhammad Zaidan; Abu Bakar, Saiful Anuar; Khisbullah, Hudha; Mohd Samin, Pakharuddin (Penerbit Universiti Malaysia Pahang, 2024)
This study presents a novel hybrid control strategy for the active hitch system, named the Dynamic Hitch Lift (DHIL), comprising a hybrid controller and a force actuator. The controller was designed to mitigate longitudinal load transfer in heavy combination vehicles by reducing the semitrailer pitch rate and rejecting the pitch moment, assisted by the virtual Skyhook moment. The new controller can calculate the desired force of the DHIL actuator to counter incoming load transfer during harsh braking exceeding 0.5 g braking deceleration. The proposed controller was assessed using a verified 12-degrees-of-freedom tractor-semitrailer model in harsh braking tests across different vehicle configurations. The first evaluation involved a stability test to demonstrate the stability of the controller in reducing load transfer across different vehicle configurations. The second evaluation was on controller performance, which revealed that the dynamic vehicle response has efficiently reduced load transfer by up to 9.14%. The third evaluation has focused on the DHIL actuator performance, which indicated that the actuator generated a force of 159, 197 N, which translated into a stepper motor torque of 1, 695 Nm at a speed of 1, 000 rpm. Simulation results affirmed that the proposed DHIL controller was stable and could effectively reduce longitudinal load transfer in heavy combination vehicles during harsh braking.